Establishment of a Brackish Water Infiltration Model and Infiltration Parameter Correction Model Considering Solute Potential - Liu, Yu; Liu, Ye; Huang, Tingting; He, Yimei; Nie, Weibo; Wang, Yongqiang; Ma, Xiaoyi (Water resources research, 2025)
Water–salt movement is a central issue in soil, water, and crop science, with its accurate simulation holding significant scientific value. The combined Richards equation for water movement and the continuity equation for solute migration currently provide a systematic approach for simulating water–salt movement. However, existing models and methods do not adequately address the theoretical effect of solute potential differences induced by soil salinity changes on water movement in practical applications. This study focuses on the infiltration of brackish water containing NaCl, integrating the semi‐permeable membrane theory from physical chemistry. A theoretical method for calculating the osmotic efficiency coefficient was introduced. In addition, a soil water–solute kinetic model and solution method, considering the influence of solute potential, were constructed. The applicability of the model was validated by comparing the simulation and experimental results, including infiltration curves, water–salt distributions, and water potentials in three soils subjected to different brackish water–salt concentrations. Subsequently, the infiltration curves and water–salt distribution characteristics of four typical soils under varying initial water contents and salt concentrations were simulated to elucidate the mechanism of coupled water–salt movement, thereby expanding the theory of water–salt dynamics. Furthermore, a correction model for infiltration parameters based on the Kostiakov equation was developed, incorporating the soil‐specific surface area, initial volumetric water content, and brackish water–salt concentration. This model enabled the conversion of infiltration parameters between brackish water and freshwater conditions. The study provides novel theoretical methods and tools for simulating soil infiltration under brackish water irrigation. Plain Language Summary Brackish water irrigation is increasingly used to alleviate freshwater shortages; however, its impact on soil water movement remains insufficiently understood. A key factor influencing infiltration under brackish water irrigation is solute potential, which affects soil water movement and distribution but is often overlooked in traditional models. In this study, we develop the first soil water–solute kinetic model that systematically quantifies the feedback mechanism of solute potential on coupled water and salt transport by integrating semi‐permeable membrane theory from physical chemistry. Using experimental data, we demonstrate that our approach significantly improves model performance across different soil types and salinity levels. Furthermore, we apply this model to calibrate the infiltration parameters of the Kostiakov model, enhancing its accuracy in simulating infiltration under brackish water irrigation. Our findings highlight that neglecting solute potential can lead to significant errors in estimating infiltration rates, potentially misguiding irrigation planning and water resource management. By incorporating solute potential into the soil water–salt movement model, this study provides more reliable scientific support and simulation tools for optimizing brackish water irrigation strategies and reducing salinization risks. Key Points The osmotic efficiency coefficient was determined using the semi‐permeable membrane theory from physical chemistry A soil water–solute kinetic model considering the influence of solute potential effects was constructed and its applicability verified Corrected infiltration parameters in the Kostiakov model under brackish water irrigation conditions